2000
DOI: 10.4049/jimmunol.164.5.2718
|View full text |Cite
|
Sign up to set email alerts
|

T Lymphocytes Activated by Persistent Viral Infection Differentially Modify the Expression of Metalloproteinases and Their Endogenous Inhibitors, TIMPs, in Human Astrocytes: Relevance to HTLV-I-Induced Neurological Disease

Abstract: Activation of T lymphocytes by human pathogens is a key step in the development of immune-mediated neurologic diseases. Because of their ability to invade the CNS and their increased secretion of proinflammatory cytokines, activated CD4+ T cells are thought to play a crucial role in pathogenesis. In the present study, we examined the expression of inflammatory mediators the cytokine-induced metalloproteinases (MMP-2, -3, and -9) and their endogenous inhibitors, tissue inhibitors of metalloproteinases (TIMP-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 59 publications
4
33
0
6
Order By: Relevance
“…An MMP/ TIMP imbalance may also be involved in the virally induced neural damage seen in patients suffering from viral meningitis or human immunodeficiency virus (HIV)-associated encephalitis (13,34) and in patients suffering from tropical spastic paraparesis/human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy (TSP/HAM) (20,23). Indeed, our previous work has shown that MMP-9 and TIMP-3 are preferentially upregulated in the cerebrospinal fluid (CSF) and parenchyma of TSP/HAM patients compared to that in asymptomatic virus carriers (35), these data being consistent with the upregulation of MMP-3, MMP-9, TIMP-1, and TIMP-3 expression seen in neural cells following contact with HTLV-1-infected T lymphocytes (21,22).…”
supporting
confidence: 74%
“…An MMP/ TIMP imbalance may also be involved in the virally induced neural damage seen in patients suffering from viral meningitis or human immunodeficiency virus (HIV)-associated encephalitis (13,34) and in patients suffering from tropical spastic paraparesis/human T-cell leukemia virus type 1 (HTLV-1)-associated myelopathy (TSP/HAM) (20,23). Indeed, our previous work has shown that MMP-9 and TIMP-3 are preferentially upregulated in the cerebrospinal fluid (CSF) and parenchyma of TSP/HAM patients compared to that in asymptomatic virus carriers (35), these data being consistent with the upregulation of MMP-3, MMP-9, TIMP-1, and TIMP-3 expression seen in neural cells following contact with HTLV-1-infected T lymphocytes (21,22).…”
supporting
confidence: 74%
“…7G) of spinal cord from patient with high inflammation level (case 1). Interestingly, we had detected the matrix metalloproteinase-9 within astrocytosis in the spinal cord of this patient (35). In contrast, the few CD45RO-positive cells present in spinal cords of nonneuroinflammatory patients were all CD100 negative (two cases studied; data not shown).…”
Section: Scd100-and Cd100-expressing T Cells In Patients With Neuroinmentioning
confidence: 91%
“…Oligodendrocytes were identified in the rat primary glial culture by immunofluorescence on culture slide or by flow cytometry (5,35), with antiCNPase (Sigma-Aldrich, St. Louis, MO), anti-GalCer, anti-NG2 (Chemicon International, Temecula, CA), anti-myelin-associated glycoprotein (Boehringer Mannheim, Indianapolis, IN), and anti-myelin basic protein (Serotec, Oxford, U.K.) mAbs. Astrocytes were identified in the same conditions with a rabbit polyclonal Ab (anti-GFAP; DAKO, Carpenteria, CA).…”
Section: Immunodetectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may indicate that MMP-TIMP complexes form during inflammation. Astrocytes are an important source of TIMP activity [15,16], and a net balance between MMPs and TIMPs may be involved in the pathogenesis of CNS disease [17]. In addition to inhibiting MMPs, TIMPs are multifunctional molecules that have distinct biological roles [18].…”
Section: Discussionmentioning
confidence: 99%